Distinctive features and types of interrelation between the indices of emotional and volitional personality sphere - Kyrylenko, Taisa; Shamlyan, Karina (Journal of Education Culture and Society, 2020)
This article deals with the role of emotions in the will activity of the personality. The analysis of the empirical study results shows that appraisal of the role of emotional experience depends on the level of will development of the individuals under study. A methodical technique has been applied, by which the indices of the emotional and volitional sphere are considered throughout different life periods of the individuals under study. Types of interrelation between the indices of will and emotions are highlighted which illustrate certain variants of the influence of emotional experience on the formation of the will structure of the personality.